2010
DOI: 10.1080/14786410903417378
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular friendly natural products: a promising approach in the management of CVD

Abstract: Natural products play an important role as nutritional supplements and provide potential health benefits in cardiovascular diseases (CVD). Compiling data from experimental, epidemiological and clinical studies indicates that dietary nutrients have profound cardioprotective effects in the primary as well as secondary prevention of coronary heart disease, hence they are considered as cardiovascular friendly natural products. The mechanism of cardioprotection produced by dietary nutritional supplements such as fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 159 publications
0
61
0
Order By: Relevance
“…It has a strong antioxidant property and has been shown to reduce the risk of cancer mainly breast, prostate and pancreas [21]. Lycopene also has protective effect in various chronic conditions like cardiovascular disease (CVD), coronary heart disease (CHD) and atherosclerosis [22,23]. Higher plasma lycopene concentrations are associated with lower risk of CVD in women which is mediated through regulation of cholesterol metabolism [24].…”
Section: Introductionmentioning
confidence: 99%
“…It has a strong antioxidant property and has been shown to reduce the risk of cancer mainly breast, prostate and pancreas [21]. Lycopene also has protective effect in various chronic conditions like cardiovascular disease (CVD), coronary heart disease (CHD) and atherosclerosis [22,23]. Higher plasma lycopene concentrations are associated with lower risk of CVD in women which is mediated through regulation of cholesterol metabolism [24].…”
Section: Introductionmentioning
confidence: 99%
“…Increases glucose uptake by skeletal muscle cells in an AMPK-dependent manner [204]. Cardiovascular friendly [208]. Anti-atherogenic bioactivities; inhibiting monocyte-to-macrophage differentiation and foam cell formation as well as hypolipidemic activity via enhancing LDL receptor gene expression and activity and decreasing acyl CoA: diacylglycerol acyltransferase 2 expression in HepG2 liver cells [207] Alkaloids, flavonoids, cardiac glycosides, tannins, and saponin [200].…”
mentioning
confidence: 99%
“…Interestingly, these may not be sufficiently robust or reliable as predictors of new cases of CVD (5,6) suggesting that protective factors exist that act to counteract and mitigate the deleterious consequences of the major CVD risk factors. In support of this possibility, recent data have shown that certain diet and dietderived chemicals may play a role in reducing and ameliorating the damage induced by exposure to risk factors of CVD (7)(8)(9)(10). Therefore, the discovery and identification of protective dietary factors and elucidation of the mechanisms by which they confer cardioprotection may be envisaged to shed light on new CVD management strategies.…”
Section: Introductionmentioning
confidence: 98%